1973
DOI: 10.1073/pnas.70.6.1790
|View full text |Cite|
|
Sign up to set email alerts
|

Aminoacid Sequence of Dogfish M 4 Lactate Dehydrogenase

Abstract: About 80% of the aminoacid sequence of dogfish (Squalus acanthius) M4 lactate dehydrogenase (EC 1.1.1.27) has been elucidated. Several sequence homologies with peptides from pig H4 and pig M4 lactate dehydrogenase are identified. Histidine 195 is homologous to the essential histidine residue in pig H4 lactate dehydrogenase. Similarities in the sequence around the "essential" cysteine residue of lactate dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, and yeast and liver alcohol dehydrogenases are delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Certain sections of protein amino acid sequences are well-conserved between homologous proteins and between proteins with similar functions, but which are coded by different gene loci (analogous proteins; see Dayhoff, 1972). X-ray diffraction studies have demonstrated several of these well-conserved sequences in active sites and in areas which are important for determining conformational folding (Buehner et al, 1973 ;Taylor et al , 1973;Rossmann et al, 1974) . As suggested by King and Jukes (1969), non-conservative amino acid substitutions in these regions are likely to produce dramatic changes in protein function, while amino acid sub stitutions in other, less-conserved sequences may produce no detectable change in enzyme function.…”
Section: Resultsmentioning
confidence: 99%
“…Certain sections of protein amino acid sequences are well-conserved between homologous proteins and between proteins with similar functions, but which are coded by different gene loci (analogous proteins; see Dayhoff, 1972). X-ray diffraction studies have demonstrated several of these well-conserved sequences in active sites and in areas which are important for determining conformational folding (Buehner et al, 1973 ;Taylor et al , 1973;Rossmann et al, 1974) . As suggested by King and Jukes (1969), non-conservative amino acid substitutions in these regions are likely to produce dramatic changes in protein function, while amino acid sub stitutions in other, less-conserved sequences may produce no detectable change in enzyme function.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the maize enzyme is similar to other M D H s in regions related to enzymatic function. Like mitochondrial N A D -M D H s [20], cytosolic N A D -M D H s [33], and lactate dehydrogenases [3,35], the chloroplastic N A D P -M D H contains a region of conserved residues (I-W-G-N-H) around what is likely to be the active site histidine (his-215 in maize). An aspartate (asp-187) that is likely to interact with this active site histidine in a proton relay system is also conserved in all of these enzymes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenases are important enzymes in anaerobic metabolism, by interconverting lactate to pyruvate utilizing NAD(P)/NAD(P)(H) (Holbrook et al, 1975). A highly-conserved cysteine residue, Cys-165 located at the proximity of co-substrate binding site (Taylor et al, 1973) possibly allowed its selection into our purification protocol. Oxidative stress has been shown to overexpress lactate dehydrogenase favouring anaerobic respiration instead of bringing it down (Oliveira & Oliveira, 2002).…”
Section: Discussionmentioning
confidence: 99%